(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines effective strategies and techniques for teaching writing in foreign language education. It highlights writing as a complex skill that integrates cognitive, linguistic, communicative, and social competences. The paper emphasizes a multi-stage process approach, including pre-writing, drafting, revising, and editing, as well as the importance of collaborative writing, peer feedback, technology integration, and individualized instruction. The study concludes that a comprehensive and student-centered approach significantly enhances learners’ writing competence and confidence.